Determinants of FDI inflows into the Baltic countries: Empirical evidence from a gravity model - Svetlana Raudonen; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The article analyzes FDI inflows into Baltic countries using a gravity approach. The results of the empirical estimation allow us to explain how difference in corporate taxation between countries, geographical and cultural distance, institutions such as regulations and the size of the economy as well as its economic development affect FDI inflows into the Baltic countries. The influence of corporate taxation on FDI flows, expressed as corporate tax rate differences between investor and host countries is statistically significant. Larger geographical distance between the countries reduces FDI flows, and institutional variables such as the economic freedom index have significant impact and affect positively FDI into the Baltics. Finally, the size of economy, measured by GDP, impacts positively the FDI flows into Baltic countries.
Keywords: E2; F2; H2; 330; gravity model; foreign direct investments; corporate tax; Baltic countries; Direktinvestition; Ausländisch; Gravitationsmodell; Schätzung; Nordosteuropa